Valuing ecosystem services applying indigenous perspectives from a global biodiversity hotspot, the Western Ghats, India - Balasubramanian, M.; Sangha, Kamaljit K. (Frontiers in Ecology and Evolution, 2023)
Estimating the value of ecosystem services (ES) helps inform policies, development programs, and promote sustainable use and management of forest resources. The Western Ghats—a global biodiversity hotspot in southern India—contribute significantly to the well-being of Indigenous and local communities (IPLCs) by providing a range of ES. In this paper we aim to assess the value of ES from the Western Ghats, applying IPLCs perspectives, to inform policy decision-making for understanding their role in people’s well-being. We estimate the value of ES applying various monetary (e.g. direct cost using production function) and non-monetary (e.g. revealed preferences using replacement or travel cost) valuation methods. The main ES include provisioning services—Non-Timber Forest Products & water; regulating services—soil erosion prevention & carbon sequestration; and cultural services. The estimated economic value of ES, at US$ 612 million (2021 values), suggests that conserving Ghat’s ecosystems is vital for supporting tribal peoples’ well-being, delivering ES to the mainstream population, and for protecting biodiversity. To date, lack of such understanding has often led to development programs that largely omit natural resources and tribal well-being connections. This study can inform future policies by offering a better and in-depth understanding of the role of ES in supporting Indigenous well-being, and underlines Ghat’s economic importance for non-marketable values which are often ignored for policy decision-making. Understanding these values will help the policy-makers to integrate the role of ES in policy planning, and design suitable development and conservation programs that protect a diverse range of ecosystems in the Western Ghats and elsewhere as well as support the sustainable living of many IPLCs/Adivasi communities across the globe.